CRITICAL PEDAGOGICS IN THE VIEW OF H.A.R TILAAR AND ITS RELEVANCE FOR NATIONAL EDUCATION - Sadewo, Barry (JURNAL ASIK, 2024)
The research was conducted to find out how the critical pedagogic concept in the view of Prof. H.A.R. Tilaar and its relevance to national education. The purpose of conducting this research is because nowadays, on this day of a very fast globalization, besides its usefulness, it also causes several problems, including the loss of direction from national diversity and dehumanization. It is challenging to require a form of critical reflective attitude that is presented to the community. This effort can very effectively occur if there is a transformation in education. The change from traditional pedagogy to critical pedagogy is an alternative way of dealing with globalization. The methodology used is descriptive qualitative methodology which makes literature study and document collection the primary thing in data collection. The findings of this critical pedagogic research are in fact still very much needed and further encouraged in its concrete application to answer the challenges of globalization and to meet the golden Indonesia 2045.